HUBUNGAN KADAR LEUKOSIT DENGAN KEJADIAN APPENDISITIS AKUT - br. Manik, Maria Magdalena; Butar-Butar, Harry; Surjani, Lylys (Universitas Methodist Indonesia, 2021)
Background: Acute appendicitis is an acute inflammation and infection of the vermiform appendix, which is simply referred to as the appendix. Appendicitis is the most common cause of acute abdominal pain and requires immediate surgery to prevent complications. The initial symptom is almost always abdominal pain, but sometimes there is no pain in the epigastrium, but there is constipation so that patients are often diagnosed late, therefore, investigations in the form of leukocyte count can help in diagnosing patientst. Objective to determine the increase in leukocyte levels in patients with acute appendicitis. Methods: This type of research is a study using the Literature Riview method. Conclusion: Based on the results of the Literature Review in 15 journals regarding the relationship between leukocyte levels and the incidence of acute appendicitis, it can be concluded that there is a significant relationship between increased leukocyte levels and the incidence of acute appendicitis.